HP30‐2, a mitochondrial PRAT protein for import of signal sequence‐less precursor proteins in Arabidopsis thaliana. Issue 8 (30th June 2017) - Rossig, Claudia; Gray, John; Valdes, Oscar; Rustgi, Sachin; von Wettstein, Diter; Reinbothe, Christiane; Reinbothe, Steffen
Abstract: Chloroplasts and mitochondria contain a family of putative preprotein and amino acid transporters designated PRAT. Here, we analyzed the role of two previously characterized PRAT protein family members, encoded by At3g49560 (HP30) and At5g24650 (HP30‐2), in planta using a combination of genetic, cell biological and biochemical approaches. Expression studies and green fluorescent protein tagging identified HP30‐2 both in chloroplasts and mitochondria, whereas HP30 was located exclusively in chloroplasts. Biochemical evidence was obtained for an association of mitochondrial HP30‐2 with two distinct protein complexes, one containing the inner membrane translocase TIM22 and the other containing an alternative NAD(P)H dehydrogenase subunit (NDC1) implicated in a respiratory complex 1‐like electron transport chain. Through its association with TIM22, HP30‐2 is involved in the uptake of carrier proteins and other, hydrophobic membrane proteins lacking cleavable NH2 ‐terminal presequences, whereas HP30‐2's interaction with NDC1 may permit controlling mitochondrial biogenesis and activity. Abstract : Chloroplasts and mitochondria are semi‐autonomous cell organelles that need to import most of their proteins from the cyotosol. Here, we report on a protein belonging to the family of preprotein and amino acid transporters designated PRAT that operates in the translocation of transit sequence‐less precursor proteins into both organelle types.